SLPI deficiency alters airway protease activity and induces cell recruitment in a model of muco-obstructive lung disease - Brown, Ryan; Dougan, Caoifa; Ferris, Peter; Delaney, Rebecca; Houston, Claire J.; Rodgers, Aoife; Downey, Damian G.; Mall, Marcus A.; Connolly, Bronwen; Small, Donna; Weldon, Sinéad; Taggart, Clifford C. (Frontiers in Immunology, 2024)
Secretory leukocyte protease inhibitor (SLPI) is an important cationic protein involved in innate airway immunity and highly expressed in mucosal secretions, shown to target and inhibit neutrophil elastase (NE), cathepsin G and trypsin activity to limit proteolytic activity. In addition to the potent antiprotease activity, SLPI has been demonstrated to exert a direct anti-inflammatory effect, which is mediated via increased inhibition and competitive binding of NF-B, regulating immune responses through limiting transcription of pro-inflammatory gene targets. In muco-obstructive lung disorders, such as Chronic Obstructive Pulmonary Disease (COPD) and Cystic Fibrosis (CF), there is an observed elevation in airway SLPI protein concentrations as a result of increased lung inflammation and disease progression. However, studies have identified COPD patients presenting with diminished SLPI concentrations. Furthermore, there is a decrease in SLPI concentrations through cleavage and subsequent inactivation by NE degradation in Pseudomonas aeruginosa infected people with CF (pwCF). These observations suggest reduced SLPI protein levels may contribute to the compromising of airway immunity indicating a potential role of decreased SLPI levels in the pathogenesis of mucoobstructive lung disease. The Beta Epithelial Na+ Channel transgenic (ENaC-Tg) mouse model phenotype exhibits characteristics which replicate the pathological features observed in conditions such as COPD and CF, including mucus accumulation, alterations in airway morphology and increased pulmonary inflammation. To evaluate the effect of SLPI in muco-obstructive pulmonary disease, ENaC-Tg mice were crossed with SLPI knock-out (SLPI -/-) mice, generating a ENaC-Tg/ SLPI -/- colony to further investigate the role of SLPI in chronic lung disease and determine the effect of its ablation on disease pathogenesis.